2006
DOI: 10.1016/j.aim.2006.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Motivic integration over Deligne–Mumford stacks

Abstract: The aim of this article is to develop the theory of motivic integration over Deligne-Mumford stacks and to apply it to the birational geometry of Deligne-Mumford stacks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
83
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 26 publications
4
83
0
Order By: Relevance
“…A slightly different version was obtained by Denef-Loeser [DL02] over a field of characteristic zero containing all ♯Γ-th roots of unity with Γ the given finite group. Yasuda [Yas06] then generalized it to an arbitrary perfect field of characteristic prime to ♯Γ. Now we recall these results.…”
Section: The Mckay Correspondencementioning
confidence: 99%
See 3 more Smart Citations
“…A slightly different version was obtained by Denef-Loeser [DL02] over a field of characteristic zero containing all ♯Γ-th roots of unity with Γ the given finite group. Yasuda [Yas06] then generalized it to an arbitrary perfect field of characteristic prime to ♯Γ. Now we recall these results.…”
Section: The Mckay Correspondencementioning
confidence: 99%
“…To deduce the general case of the theorem from a result in [Yas06], we need to first prove Theorem 5.9 below.…”
Section: The Mckay Correspondencementioning
confidence: 99%
See 2 more Smart Citations
“…When P is reflexive, Batyrev and Dais [3] showed that δ i is the 2ith stringy Betti number of a toric variety X associated to P . Furthermore, in this case, results of Yasuda [31] imply that δ i is equal to the dimension of the 2ith orbifold cohomology group of the canonical orbifold associated to X. This interpretation of the Ehrhart δ-polynomial of P was used by Mustaţǎ and Payne in [23] and Karu in [18].…”
Section: Introductionmentioning
confidence: 89%